Jun ware glaze colours: An X-ray absorption spectroscopy study. Issue 6 (June 2022) - Yuan, Mingyue; Hou, Jiayu; Gorni, Giulio; Crespo, Daniel; Li, Yuan; Pradell, Trinitat
Abstract: Jun ware is stoneware created in the late Northern Song dynasty (12 th century) with a blue glaze combining transparent-blue and whitish-opaque submillimetric areas. The glaze has a glass nanostructure with lime-rich droplets in a silica-rich matrix resulting from a high temperature liquid-liquid phase separation. Calcium-rich opaque and calcium-poor transparent areas are combined. Iron is more oxidised in the calcium rich areas (≈17–20% Fe 2+ ) than in the calcium poor areas (≈60–70% Fe 2+ ) of the glaze. Therefore, iron is oxidised in the lime-rich droplets and reduced in the silica-rich matrix. The sky- like appearance of the glaze is due to the combination of the light absorption in the transparent-dark-blue Fe 2+ rich areas and scattering in the white-yellowish Fe 3+ rich areas. Copper appears mainly oxidised but in the red areas a few small copper nanoparticles are present and iron appears more oxidised. The result indicates the simultaneous reduction of copper and oxidation of iron. Highlights: Lime-rich and silica-rich glass nanostructure. Iron is mainly oxidised in the lime-rich droplets and reduced in the silica matrix. Copper is mainly present as Cu+. Simultaneous reduction of copper and oxidation of iron in the red areas.